The hepatocurative effect of artichoke extracts on acute paracetamol toxicity in experimental mice - احمد هلا; نعمى حسن; ديما محمد (Latakia University Journal -Medical Sciences Series, 2024)
The artichoke is considered an important medicinal plant, rich in phenolic compounds that act as antioxidants. It is known for its hepatoprotective effect, and its leaves are widely used for its benefits on the digestive system. There are not many studies on its hepatocurative effect on the liver. Therefore, we prepared extracts from different parts of the plant (bracts and leaves), determined their total phenolic compounds and then studied their hepatocurative effect in experimental mice after inducing hepatotoxicity with a single dose of paracetamol 300mg/kg intraperitoneal injection (IP). After an hour of the poisoning, the extracts were administrated orally to the mice at a dose of 1g/kg. Then, 6 hours after the poisoning, the mice were anesthetized, and blood samples were drawn from the heart in order to analyze the liver enzymes ALT, AST. Thereafter, the mice were dissected, and livers were taken for histological analysis. Our results indicate the hepatocurative effect of the artichoke leaves extract, as this extract caused statistically significant decrease (p≤0.05) in ALT and AST values compared to the pathological control, while the bracts extract had a less significant effect on AST values than the leaves extract, and it did not have a statistically significant effect on ALT values.